2019
DOI: 10.1002/bsl.2428
|View full text |Cite
|
Sign up to set email alerts
|

Remorse in psychotic violent offenders: An overvalued idea?

Abstract: Expressing remorse – or not – appears to influence criminal justice outcomes, but preliminary exploration of both judicial and psychological concepts suggests they lack clarity. We asked the following questions: does psychosis impair capacity for, or expression of, remorse for a homicide or other serious harm to others? Is failure to express remorse for an offence associated with recidivism? We conducted systematic reviews of empirical literature on remorse for serious violence while psychotic, and on relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…In the first of the studies, the guilt feelings of young men who went to prison were examined. Here, slightly less than half were found to feel guilty [30]. But after his or her release from prison, his or her feelings of guilt gradually decreased.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the first of the studies, the guilt feelings of young men who went to prison were examined. Here, slightly less than half were found to feel guilty [30]. But after his or her release from prison, his or her feelings of guilt gradually decreased.…”
Section: Discussionmentioning
confidence: 90%
“…Here, it was concluded that there is a relationship between delinquency and remorse, but this relationship is not specific to psychosis. Also, it was found that only two studies were conducted on remorse/guilt for a particular crime and whether or not to commit a crime again [30,31]. In the first of the studies, the guilt feelings of young men who went to prison were examined.…”
Section: Discussionmentioning
confidence: 99%
“…It seems logical to expect that someone who becomes genuinely remorseful would be less likely to reoffend and more likely to become a good citizen but evidence is slight that remorse or ‘self-culpability’ is associated with good outcomes. 1 Of interest, however, is that, although blaming external factors for a crime reduces guilt feelings, blaming mental illness does not;* perhaps an offender's accurate attribution of an offence to mental disorder facilitates his/her true acceptance of treatment needs, and improved safety through treatment. Such processing, however, takes time and therapy; it is unlikely at the time of sentencing.…”
Section: Gaps In Evidence For Sentencers and Psychiatristsmentioning
confidence: 99%
“…During presentencing meetings, a probation officer may attempt to correctly read a defendant’s speech, related tone and cadence, nonverbal demeanor, and other behaviors when assessing his remorse (Hanan, 2018). However, this process could be affected by the symptomatic presentation of a defendant’s psychiatric disorder, as well as an officer’s own assumptions about mental illness or the defendant’s capacity to experience remorse (Dandawate et al, 2019). Sometimes these disorders have been previously formally diagnosed, and this is included in a defendant’s file; in other instances, a defendant may be exhibiting symptoms associated with a psychiatric diagnosis that has yet to be diagnosed or will at some point be diagnosed during the legal process (Berryessa, 2019).…”
mentioning
confidence: 99%